Urban community development - Thudipara,Jacob Z (Jaipur, 2008)
"Urban Community Development (UCD) has been considered as one of the effective means of working with the urban poor right from 1958 when the first pilot project in UCD was started. In spite of the numerous other projects and nearly fifty years of experience, there is not enough literature available on the subject in the Indian context. As a result, there is a lack of conceptual clarity as to what is meant by this approach. Therefore, one finds that undue emphasis is laid on to the material aspect of the development, and the human factor, i.e., developing the inner potentials and empowering the people to tackle their own problems is given a back seat. This book is the outcome of two decades of teaching, consultancy and research by the author in the field of community development. An attempt is made here to put forward a balanced view of community development, with an emphasis on people's participation and self-help. It is further enriched by providing well-documented case studies and practice-based research studies. It is hoped that this book will be of special use to planners, policy makers, trainers and human services professionals who are concerned with urban development."
Keywords: Urbanization-India